The effects of implementation of religion and spiritual elements in the counselling process - Mohd Saleh, Nur Diyanah; Mohamad Yusop, Yusni; Nor Zainudin, Zaida; Wan Othman, Wan Norhayati (Human Resource Management Academic Research Society, 2021)
The implementation of religion and spiritual elements in the counselling process has received attention from researchers and individuals from this area. This systematic review explores the effectiveness of this implementation on clients who had undergone counselling sessions. This systematic review is conducted following Preferred Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. A few electronic databases have been used such as Ebcohost, ProQuest and Sage Journals. Moreover, the Google Scholar website is also utilized in this review. The term used in the searching process is “Effect”, “Spiritual” “Counselling” and other relevant provenance focusing on advantages of the inclusion of religion and spiritual elements in counselling process. There are different countries involved in this systematic review and 15 journal articles extracted have been reviewed. Results showed that utilizing the religion and spiritual elements in counselling process had led to the beneficial effects to the clients.